Bacillus aryabhattai E ORGANOMINERAL AFERT NO DESENVOLVIMENTO DE HÍBRIDO DE MILHO NO CERRADO-MATO-GROSSENSE - de Freitas Lima , Gabriel; Gonzalez Aguilera , Jorge; Maas , Adriano; Alves Ferreira , Talita; Costa Martins , Werverth (ANAIS DO ENIC, 2026)
-